Infrastructure for Improved Rural Livelihoods - Brushett, Stephen; John-Abraham, Indu (World Bank, Washington, DC, 2012)
This article highlights some of the findings from recent analytical work that has been carried out in the Latin America and Caribbean (LAC) region, notably a number of promising practices that are being developed to effectively address the infrastructure provision challenge, and in particular to ensure that infrastructure increases rural competitiveness and incomes.